Exploring the Intersection of Pancasila and Human Rights in Indonesian Law - Santy, Santy (Sinergi International Journal of Education, 2024)
This research aims to explore the intersection of Pancasila and human rights in Indonesian law . The research investigates how Pancasila, as the foundational philosophy of Indonesia, can be aligned with the principles of human rights as enshrined in internationalhuman rights instruments . Methode The research methodology includes a comprehensive analysis of relevant Indonesian laws, constitutional provisions, and international human rights standards. The research also utilizes a comparative approach, examining how other countries have integrated their national philosophies with human rights principles .The findings of this research highlight the potential harmonization between Pancasila and human rights principles in Indonesian law . By recognizing the fundamental values of Pancasila, such as social justice, unity, and religious freedom, Indonesian law can uphold and protect human rights forall individuals within the country.Through the alignment of Pancasila with international human rights standards, Indonesia can ensure that its legal framework promotes and protects the fundamental rights and freedoms of all. Implication for Student research provides a unique opportunity to engage in critical thinking and analysis of the ethical and legal frameworks that shape their country. By delving into case studies and legislative decisions, students can develop a nuanced understanding of how Pancasila influences the interpretation and application of human rights laws, thereby fostering a more informed and empowered citizenry.